Milking machines - Watkins, Warren Elmer (My University, 1906)
Introduction: During the last fifty years the dairy industry has developed so rapidly that it is now regarded as one of the chief sources of revenue for the modern farmer. This is due largely to the ever increasing number of dairy machines and appliances, as well as improved methods of breeding and feeding, a more thorough knowledge of the intricate details in the production of sanitary dairy products and the business ability of the dairyman as displayed in creating and maintaining desirable markets. As a good dairy is a constant source of revenue, maximum production at the minimum cost has ever been the goal toward which the dairy farmer has been constantly striving. Many appliances and machines have been perfected, which have completely revolutionized the dairy business. The value of the Babcock tester, milk separator and pasteurizer can scarcely be estimated; they are absolutely essential to the complete modern dairy. Although inventors have been very successful along this line, yet the difficulties have been almost insurmountable in the creation of an efficient sanitary appliance for drawing milk from the cow's udder. Milking machines or appliances may be classified under three heads: (1). The milking tube. (2). Pressure machines operated by springs and levers. (3). Machines which extract the milk by means of pressure and suction combined. For a long time straws have been inserted into the main duct of cows' teats to draw out the milk, but they were often the cause of injury to the udder and a source of contamination of the milk. One of the first tubes placed on the market was invented by George of New York in 1878, and consisted of a teat tube or tubes having a number of small holes through which the milk entered and a flaring end for increasing the flow of milk without unduly stretching the teat.
Citation: Watkins, Warren Elmer. Milking machines. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Dairy; Milking Machine; Theses